Behaviour of cervical cancer prevention among fertile age woman: health promotion approach - Ni Ketut Alit Armini; Elida Ulfiana; Kartika Indaswari Dewi; Julinda Malehere (International Journal of Public Health Science (IJPHS), 2022)
Cervical cancer incidences have tremendous effects on patients' quality of life and their families and affect government health expenditure. Prevention and early detection action are urgently needed. This study aimed to analyze the prevention behavior of cervical cancer of fertile ages women based on the Health Promotion Model. This study involved 196 samples taken by cluster sampling. Independent variables included personal factors, including ages, perceived health status and culture, perceived benefits, perceived barriers, self-efficacy and attitudes related to activities, husband's support, and situational influences. The dependent variable was the behavior of cervical cancer prevention. Data were collected using a questionnaire then analyzed by logistic regression with α<0.05. There was a relationship between perceived barriers (p=0.004) and situational influences (p=0.021) with cervical cancer prevention behavior. However, there is no relationship between personal factors, perceived benefits, self-efficacy, attitudes related to activity, and husband's support. Further research can be conducted through a qualitative framework to explore cervical cancer prevention of fertile age’s women.